Caracterización experimental y numérica de la articulación del hombro en la técnica del estilo de crol en natación - Hernández Gil, Marcos Javier; Orús, Jorge Grasa; Marín Zurdo, José Javier (Jornada de Jóvenes Investigadores del I3A, 2019)
With the help of the systems and optical markers, it is possible to characterize the three-dimensional movement, in this case, the shoulder joint during the front-Crawl stroke under laboratory condition outside the water, to later simulate its biomechanical behavior using the finite element method (FEM).